Mean FN or SPL for each of the three frequency bands for each site. - Martin P. Volaric (20988070) (2025)
Datapoints represent mean of 15 min averages ±  SD. (A) FN <  100 Hz, (B) 150 Hz < SPLMID <  1500 Hz, (C) SPLHI >  7000 Hz.